Pelatihan Service Excellence dan Business English Correspondence Bagi Staf Yayasan Kanker Anak Indonesia - Hariyani, Reni; Sofiani, Fenti; Raharjo, Didik Hariyadi; Prasetio, Tio (LPPM Universitas Bina Sarana Informatika, 2024)
The importance providing service from the heart to stakeholders noble organization or company needs to do. One of them is service excellence provided to cancer patients, especially children. Apart from that, to collaborate with external parties, Yayasan Kanker Anak Indonesia (YKAI) requires English business correspondence with members of Childhood Cancer International. This training aims to improve service excellence skills for YKAI staff and increase understanding business correspondence in English for YKAI staff. The problem for community service partners is a lack of understanding excellent service and a lack of understanding business correspondence in English. Because the educational backgrounds the staff are different. The training method delivered using the lecture method as well discussion question and answer of delivering material online via the zoom meeting application as the evaluation measurement method implementation the abdimas by providing questionnaire with Google form to the abdimas participants including pre-test and post-test. The results implementing community service activities are reviewed from three indicators, indicator ability to implement service excellence YKAI staff increased by 35%, the indicator knowledge regarding business correspondence in English has increased by 60%, and the indicator ability to write business correspondence in English has increased by 75%. This training activity very beneficial for partners of compassion and humanity towards others.